Interactive persuasive learning for the elderly: A conceptual model - Zulkifli, Abdul Nasir; Ahmad, Mazida; Abu Bakar, Juliana Aida; Che Mat, Ruzinoor; Mohamed Noor, Nurtihah (2015)
Interactive media technology promotes self-directed and active learning approaches and has the capability to foster the learning process. Furthermore, the emergence of persuasive technology has increased the application of interactive media in learning in a variety of ways. Persuasive technology can be implemented in the design and development of a computer application that can persuade users to change their attitudes and behaviours so as to accelerate the learning process. The aim of this paper is to develop a conceptual model of an interactive persuasive learning system to encourage the elderly to use a computer application for learning. Based on a review of the related literature on persuasive technology and interactive media, a conceptual model is developed. The proposed conceptual model will be helpful in the design and development of an interactive media system that encourages engagement in learning processes among the elderly.